(untitled) (Journal of Health, Population and Nutrition, 2013)
This paper investigates similarities and differences between abortion clients of a public-sector clinic and a non-governmental organization (NGO) clinic in Nepal. In 2010, a survey of 1,172 women was conducted in two highly-attended abortion clinics in Kathmanduone public-sector clinic and another operated by an NGO. Data on the sociodemographic characteristics of clients, their fertility preferences, and use of contraceptives were analyzed. Similarities and differences between the two groups of clients were examined by either chi-square or t-test. The clients of the two clinics were similar with respect to age (27.3±5.7 years), education (26.5% had no education), and number of living children (1.88±1.08). They differed with regard to contraceptive practice, the circumstances resulting in unintended pregnancy, and future fertility preferences. Just over 50% clients of the public and 35% clients of the NGO clinic reported use of contraceptives surrounding the time of unintended pregnancy. The groups also differed in the contraceptive methods used and in reasons for not using any method. The NGO clinic contributed principally to expanding the availability of and access to abortion services. DOI: http://dx.doi.org/10.3329/jhpn.v31i3.16830 J HEALTH POPUL NUTR 2013 Sep; 31(3): 376-387